Notes on the Occurrence of Bamboo, Gigantochloa albociliata (Munro) Kurz, from Bastar, Chattisgarh, India - Naithani, H. B.; Pal, R. C. (Indian Forester, 2006)
Gigantochloa albociliata (Munro) Kurz, a native of Myanmar and Thailand has now been reported from the wild from Kanger Valley, Wildlife Sanctuary, Bastar (Jagdalpur), Chattisgarh. It has gregariously flowered Bastar in 1960. It can easily recognized by its narrow white ciliate spikelets, and having long ligule of culm sheaths. It is often confused with Gigantochloa nigrociliata (Buse) Munro, a species endemic to Indonesia and Thailand and having long, black ciliate spikelets and culm sheaths having narrow ligule, and raised rounded auricles ending in curved sheath extension.